A supramolecular sensor array for selective immunoglobulin deficiency analysis. Issue 77 (9th September 2019) - Liu, Yang; Gill, Adam D.; Duan, Yaokai; Perez, Lizeth; Hooley, Richard J.; Zhong, Wenwan
Abstract : A host–guest based fluorescence sensor array can fully discriminate five structurally similar Ig protein isotypes, and recognize Ig deficiencies in serum. Abstract : A host–guest based fluorescence sensor array can sense small differences in protein structure. The combination of three cavitand hosts and two fluorophores to form a 4-component array is sufficient to fully discriminate five structurally similar Ig protein isotypes. The array can be applied to recognize Ig deficiencies in serum, when combined with a Protein L-based extraction process, allowing analysis of immunodeficiency in a simpler, lower cost manner than tests that require multiple specific antibodies.